2022
DOI: 10.3390/ani12192631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Linoleic Acid (18:2n-6) Supplementation on the Growth Performance, Fatty Acid Profile, and Lipid Metabolism Enzyme Activities of Coho Salmon (Oncorhynchus kisutch) Alevins

Abstract: A 12-week feeding trial aimed to evaluate the effects of dietary linoleic acid (LA, 18:2n-6) on the growth performance, fatty acid profile, and lipid metabolism enzyme activities of coho salmon (Oncorhynchus kisutch) alevins. Six experimental diets (47% crude protein and 15% crude lipid) were formulated to contain graded LA levels of 0.11%, 0.74%, 1.37%, 2.00%, 2.63%, and 3.26%. Each diet was fed to triplicate groups of 50 alevins with an initial body weight of 0.364 ± 0.002 g, which were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that the EFA demand greatly varies depending on the fsh species, growth stage, and environment of the fsh, but most studies focus on juvenile and adult fsh stages, and studies on EFAs in the early stage have not attracted enough attention [4,[17][18][19]. Currently, linoleic acid (18 : 2n-6, LA) and eicosapentaenoic acid (20:5n-3, EPA) are characterized as EFAs [20,21], there is a lack of information about the ALA requirements for this species. Terefore, this study investigated the efects of dietary ALA levels on the growth, body composition, and fatty acid profle of coho salmon alevins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the EFA demand greatly varies depending on the fsh species, growth stage, and environment of the fsh, but most studies focus on juvenile and adult fsh stages, and studies on EFAs in the early stage have not attracted enough attention [4,[17][18][19]. Currently, linoleic acid (18 : 2n-6, LA) and eicosapentaenoic acid (20:5n-3, EPA) are characterized as EFAs [20,21], there is a lack of information about the ALA requirements for this species. Terefore, this study investigated the efects of dietary ALA levels on the growth, body composition, and fatty acid profle of coho salmon alevins.…”
Section: Introductionmentioning
confidence: 99%